ANALISIS PENGARUH KEBIJAKAN PEMERINTAH DALAM MENERAPKAN PENGAMPUNAN PAJAK (TAX AMNESTY) TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA TAHUN 2016-2017 - SARI, ANITA PUSPITA (KIAT BISNIS, 2017)
This research aim to test is there any difference of mean IHSG of before and hereafter event of applying of Iease pardon (tax amnesty) at period I, period II, and period III. Research type represent the research of event study by using data sekunder having the character of quantitative publicized by BEI. Technique of Intake sampel in this research by using Technique of Purposive Sampling. Data used in this research that is IHSG at the (time) of daily closing during research period from date 21 June 2016-11 April 2017. This research use the event study, event period used is 14 day that is 7 day of before and 7 day hereafter event. Analyse to use the test t by Paired is Sample T-Test. From research result use the test t by Paired is inferential Sample T-Test that there are mean IHSG before and hereafter event of Applying of Iease Pardon (Tax Amnesty) Period I: at date of 1 July 2016 s.d 30 September 2016, Period II: at date of 1 October 2016 s.d 31 December 2016, Period III: at date of 1 January 2017 s.d 31 March 2017. Keyword: Event Study, Tax Amnesty, IHSG